Virulence Determination of Three Iranian Isolates of Salmonella Enteritidis in Day-Old Layer Chicks - Reza Tavayef; Seyed Mostafa Peighambari; Bahram Shojadoost; Omid Dezfoulian (Iranian Journal of Veterinary Medicine, 2020)
BACKGROUND: Salmonella Enteritidis (SE) infection in poultry is one of the most important concerns in poultry. Virulence and pathogenicity of the SE isolates from Iran have not been well studied so far. OBJECTIVES: In the present study, three Salmonella Enteritidis (SE) isolates were compared with a standard SE strain (PT21) for virulence in one-day-old layer chicks. All of the isolates were supposed to be virulent because of carrying a large-sized virulence plasmid. METHODS: Fifty day-old layer chicks (LSL strain) were divided into five groups of 10 chicks and raised in separate cages until 14 days of age. All three SE isolates were cultured in brain-heart infusion (BHI) broth to reach a concentration of approximately 1010 CFU/ml. The challenged groups included three groups inoculated with three SE isolates (A20, S32, S34) and one group inoculated with SE PT21 as positive control. One group was raised as negative control without receiving any bacteria. Any mortality or morbidity observed in any group was recorded. Samples were taken from liver, jejunum and cecum at days 2, 4, 6, 9 and 14 days of age, cultured for SE isolation, colony counting and histopathological examinations. RESULTS: All challenged groups showed mild to severe diarrhea in all birds and some birds were listless especially in the first week. No signs were seen in the control group. Two mortalities occurred in challenged groups. Salmonella Enteritidis was detected in all samples until the end of experiment. The colony count showed less (100 to 1000 times less) SE in liver compared to that of cecal samples. Histopathological findings also were compatible with symptoms and bacteriological results. CONCLUSIONS: We concluded that all three SE isolates were able to colonize in the digestive system of layer chicks leading to mortality or at least lower performance compared to healthy chicks